Mind Bunyan Cards: Innovation in Arabic Learning Media to Improve Simple Sentences in Writing Skill - Keysya Mahya Kamila; Wati, Ana Taqwa (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2025)
Mastery of basic Arabic sentence construction for beginners is often hindered by monotonous, memorization-focused teaching methods, creating a need for innovative approaches that facilitate creative understanding. This quasi-experimental study investigates the effectiveness of Mind Bunyan Cards, a visual tool for sentence structuring, in enhancing Arabic writing skills. Involving 42 student participants, the study compared an experimental group (using the cards) with a control group (conventional method). Test data were analyzed using ANCOVA, controlling for pre-test scores. Results showed a statistically significant difference (F(1,39) = 13.52, p = 0.001) in favor of the experimental group, with a substantial effect size (ηp² = 0.257), indicating that 25.7% of the skill improvement is attributable to the intervention. These findings validate the tool's effectiveness as an innovative learning medium that shifts the paradigm from mechanical memorization to meaningful and creative sentence formation.